Conditions for maintaining and eroding pseudo-overdominance and its contribution to inbreeding depression - Abu-Awad, Diala; Waller, Donald (Peer Community Journal, 2023)
Classical models that ignore linkage predict that deleterious recessive mutations should purge or fix within inbred populations, yet inbred populations often retain moderate to high segregating load. True overdominance could generate balancing selection strong enough to sustain inbreeding depression even within inbred populations, but this is considered rare. However, arrays of deleterious recessives linked in repulsion could generate appreciable pseudo-overdominance that would also sustain segregating load. We used simulations to explore how long pseudo-overdominant (POD) zones persist once created (e.g., by hybridization between populations fixed for alternative mildly deleterious mutations). Balanced haplotype loads, tight linkage, and moderate to strong cumulative selective effects all serve to maintain POD zones. Tight linkage is key, suggesting that such regions are most likely to arise and persist in low recombination regions (like inversions). Selection and drift unbalance the load, eventually eliminating POD zones, but this process is quite slow under strong pseudo-overdominance. Background selection accelerates the loss of weak POD zones but reinforces strong ones in inbred populations by disfavoring homozygotes. Models and empirical studies of POD dynamics within populations help us understand how POD zones may allow the load to persist, greatly affecting load dynamics and mating systems evolution